2003
DOI: 10.1080/0968763021000057727
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use by Truck Drivers in Brazil

Abstract: In Brazil, those who are suspected of driving under the influence of drugs are tested only for ethanol. Professional drivers, especially truck drivers, use stimulant drugs to prevent sleeping during long-distance driving. Surveys on the patterns of use of illicit drugs in the workplace have rarely been conducted in Brazil, in spite of the high costs and the potential risk to public health. Since 1996, the authors have been compiling the results of tests, performed in their laboratories, for drugs in urine samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 8 publications
3
18
0
9
Order By: Relevance
“…The association of amphetamine consumption with the younger age groups indicates that these are more vulnerable, possibly as a consequence of their reduced experience in the profession, which causes more diffi culty in dealing with work pressures. Greater vulnerability of young truck drivers is highlighted by Leyton et al 7 and by Silva et al, 14 who have shown higher prevalence of drug use in young drivers, as well as higher risk of depression (Silva-Júnior et al). 13 This scenario should be understood within a broader context, characterized by low-level of schooling, long periods truck drivers stay away from their homes and families and precarious working conditions, as poor conditions of the highways and of the places where they stay during their trips (gas stations, customhouses, companies' yards).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The association of amphetamine consumption with the younger age groups indicates that these are more vulnerable, possibly as a consequence of their reduced experience in the profession, which causes more diffi culty in dealing with work pressures. Greater vulnerability of young truck drivers is highlighted by Leyton et al 7 and by Silva et al, 14 who have shown higher prevalence of drug use in young drivers, as well as higher risk of depression (Silva-Júnior et al). 13 This scenario should be understood within a broader context, characterized by low-level of schooling, long periods truck drivers stay away from their homes and families and precarious working conditions, as poor conditions of the highways and of the places where they stay during their trips (gas stations, customhouses, companies' yards).…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, 16.6% of the interviewees stated having used amphetamines at least once in their lives, and 7.5% reported regular use of amphetamines to stay awake. Silva et al 14 detected the presence of amphetamines in truck drivers' urine in Southeast, Northeast and South of Brazil, with prevalence of 4.8%. The highest prevalence was observed in the South (6.0%) and the lowest, in the Northeast (3.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has also published 2 studies in this area. In 2003, urine samples collected from truck drivers (n = 728) in 3 geographical regions of Brazil revealed that 5.63 percent of the participants tested positive for the analyzed drugs (THC, amphetamines, and cocaine; Silva et al 2003). More recently, urine samples collected from 488 truck drivers in the state of São Paulo were subjected to toxicological analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries have shown that life conditions of truck drivers makes them come into contact with dangerous behavior such as having unhealthy sexual partners and drug abuse (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%